2021
DOI: 10.1097/hs9.0000000000000539
|View full text |Cite
|
Sign up to set email alerts
|

Next-generation Sequencing in Bone Marrow Failure Syndromes and Isolated Cytopenias: Experience of the Spanish Network on Bone Marrow Failure Syndromes

Abstract: Inherited bone marrow failure syndromes (IBMFSs) are a group of congenital rare diseases characterized by bone marrow failure, congenital anomalies, high genetic heterogeneity, and predisposition to cancer. Appropriate treatment and cancer surveillance ideally depend on the identification of the mutated gene. A next-generation sequencing (NGS) panel of genes could be 1 initial genetic screening test to be carried out in a comprehensive study of IBMFSs, allowing molecular detection in affected patients. We desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…38 Using an NGS panel, Galvez et al successfully diagnosed only three of 25 patients with prolonged neutropenia. 18 Overlap with primary immunodeficiencies, 49 new unrecognized genes (estimated to be the cause in about 25% of patients with SCN) 50 and acquired neutropenia probably contribute to the low yield of pathogenic variant detection among these patients. The overall poor results that we and others achieved calls for better selection of candidates for genetic diagnosis due to isolated neutropenia.…”
Section: Congenital Neutropeniamentioning
confidence: 99%
See 1 more Smart Citation
“…38 Using an NGS panel, Galvez et al successfully diagnosed only three of 25 patients with prolonged neutropenia. 18 Overlap with primary immunodeficiencies, 49 new unrecognized genes (estimated to be the cause in about 25% of patients with SCN) 50 and acquired neutropenia probably contribute to the low yield of pathogenic variant detection among these patients. The overall poor results that we and others achieved calls for better selection of candidates for genetic diagnosis due to isolated neutropenia.…”
Section: Congenital Neutropeniamentioning
confidence: 99%
“…However, due to the non-specific clinical and laboratory presentation of syndromes causing cytopenias, an unbiased diagnosis, as offered by next-generation sequencing (NGS) technologies, is usually essential. 11,15,16 Indeed, several studies have demonstrated advantages of NGS technologies for improving diagnosis, 11,13,[15][16][17][18] and reported genetic diagnostic rates of 13-54%. However, differences were evident in the patient populations (IBMFS only, MDS only, IT only or all these conditions), age (children, adults or both), sequencing method (NGS panel or whole exome sequencing [WES]), the type of variants detected (germline variants or both somatic and germline variants) and the types of sequence variants reported (pathogenic and likely pathogenic [P/LP]) only or also variants of unknown significance [VOUS]).…”
Section: Introductionmentioning
confidence: 99%
“…1 However, many patients remain underdiagnosed because of the wide range of the phenotype which overlap with other diseases. 2,3 Now with the advent of whole-exome sequencing, it is possible to identify the novel genetic defects of unclassificated BMFS in the societies with high-rate consanguinity. [1][2][3] Shwachman-Diamond syndrome (SDS) is one of BMFS related to ribosomopathies.…”
mentioning
confidence: 99%
“…2,3 Now with the advent of whole-exome sequencing, it is possible to identify the novel genetic defects of unclassificated BMFS in the societies with high-rate consanguinity. [1][2][3] Shwachman-Diamond syndrome (SDS) is one of BMFS related to ribosomopathies. 4,5 Most cases are associated with biallelic mutations in the SBDS gene.…”
mentioning
confidence: 99%
See 1 more Smart Citation